Proceedings of the 4th International Conference on Mobile Technology, Applications, and Systems and the 1st International Sympo 2007
DOI: 10.1145/1378063.1378142
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of services for the mobile tourist

Abstract: Mobile tourism services have become an essential tool for supporting tourists around the world. Our research aims to identify desirable and undesirable features for mobile tourism services from the tourists' perspective. Focus group discussions and surveys were conducted to gather tourists' needs, exploring the problems faced. This paper presents our findings highlighting desirable design features being maps and transportation information, and unpopular features such as gaming activities. The results also refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…As an example, a participant [P24] indicated that: “We managed to find quite a lot of useful information from the guidebook.” Here the participant showed that they had obtained the information from a direct source. This is consistent with an earlier study which highlighted that maps and guides are the most important features for mobile tourist applications (Tan, Goh, Theng, & Foo, ). In this phase, there were 184 influences from intergroup collaboration and 307 influences from intragroup collaboration.…”
Section: Resultssupporting
confidence: 93%
“…As an example, a participant [P24] indicated that: “We managed to find quite a lot of useful information from the guidebook.” Here the participant showed that they had obtained the information from a direct source. This is consistent with an earlier study which highlighted that maps and guides are the most important features for mobile tourist applications (Tan, Goh, Theng, & Foo, ). In this phase, there were 184 influences from intergroup collaboration and 307 influences from intragroup collaboration.…”
Section: Resultssupporting
confidence: 93%
“…A survey conducted by [20] showed that mobile travelers ranked street maps, transport, tourist destination, airport and emergency contact as most required information. The details of nearby tourist spots, such as operating hours, transportations availability, the entry price, special event/promotion, and others, should be provided in the mobile application.…”
Section: A Perception Levelmentioning
confidence: 99%
“…Although there are many mobile hospitality applications available and integrated into activities and habits of guests, it turns out that many of these services are not oriented to understand the individual needs of each hotel guest [5,6].…”
Section: Introductionmentioning
confidence: 99%